The frontal lobe and its role in the depression - Ventura, Roberto (2007)
The authors carry out an updating of the subject and present the classification of these disorders according to their lesion location and to the anatomoclinic correlation. Lastly they talk about the results in three patients treated from the neuropsyquiatric view within the framework of the above mentioned classification.